(untitled) (Universal International Scientific Journal, 2026)
Educational systems are increasingly challenged by learner variety regarding aptitude, motivation, learning styles, and socio-cultural background. Differentiation has been a primary educational method for addressing this variation. This article analyzes external and internal differentiation as two interrelated methodologies in educational philosophy and practice. Utilizing both historical and modern literature, the paper examines the functioning of structural differentiation and classroom-level instructional adaptation, their contrasting benefits and drawbacks, and their consequences for educational equity. It is contended that a balanced integration of both types of differentiation provides the most effective and inclusive approach to learner diversity